2017
DOI: 10.1001/jama.2017.3415
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serotonergic Antidepressant Use During Pregnancy and Autism Spectrum Disorder in Children

Abstract: In children born to mothers receiving public drug coverage in Ontario, Canada, in utero serotonergic antidepressant exposure compared with no exposure was not associated with autism spectrum disorder in the child. Although a causal relationship cannot be ruled out, the previously observed association may be explained by other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 39 publications
7
117
1
1
Order By: Relevance
“…The association found between psychiatric disorders in children and antidepressant exposure in utero could be attributable to the severity of the mother’s underlying disease, as the authors correctly pointed out in their study6: women who are treated are likely to have more severe and recurrent illness. Furthermore, Brown and colleagues found that use of antidepressants 90–365 days prior but not during pregnancy (recent users) was significantly associated with autism spectrum disorders (adjusted HR 1.85, 95% CI 1.37 to 2.51) 5. They explained that this evidence corroborates the hypothesis that the indication for medication may clarify the increased risks for autism spectrum disorder and not the use of antidepressant medication itself.…”
Section: What Next In Research and Concluding Remarksmentioning
confidence: 92%
See 3 more Smart Citations
“…The association found between psychiatric disorders in children and antidepressant exposure in utero could be attributable to the severity of the mother’s underlying disease, as the authors correctly pointed out in their study6: women who are treated are likely to have more severe and recurrent illness. Furthermore, Brown and colleagues found that use of antidepressants 90–365 days prior but not during pregnancy (recent users) was significantly associated with autism spectrum disorders (adjusted HR 1.85, 95% CI 1.37 to 2.51) 5. They explained that this evidence corroborates the hypothesis that the indication for medication may clarify the increased risks for autism spectrum disorder and not the use of antidepressant medication itself.…”
Section: What Next In Research and Concluding Remarksmentioning
confidence: 92%
“…Brown et al reported quite convincing data showing that the use of antidepressants before and during pregnancy in the mothers is not causally related to autism in the offspring 5. The association found between psychiatric disorders in children and antidepressant exposure in utero could be attributable to the severity of the mother’s underlying disease, as the authors correctly pointed out in their study6: women who are treated are likely to have more severe and recurrent illness.…”
Section: What Next In Research and Concluding Remarksmentioning
confidence: 98%
See 2 more Smart Citations
“…However, two very recent studies have concluded that there is no significant relationship between prenatal exposure to SSRIs and ASD risk and suggest that the previously observed association may be due to other factors [22,23].…”
Section: Review Articlementioning
confidence: 96%